ZVS based switching technique mitigates the power losses using mosfet based full bridge dc converter - Kumara Swamy, Durgam; B. V. Sanker Ram, Dr (International Journal of Engineering and Technology, 2018)
In todayâ€™s' vitality power industries Boost converters highly required to convert the normal power into improvised power. Normally vitality converters struggled with voltage pressure over the power electronics switching nature and undulation. The renewable energy of a kind that vitality Photovoltaic (PV)-cell sources, windmill and battery are the sources for the converters; in this Photovoltaic play a vital role and mostly used medium to provide converters for further processing. The vitality PV is basically acted along with solar power efficiency, which is improvised ZeroVoltage Switching [ZVS] converters. The Zero-Voltage Switching [ZVS] converters transforms the low-power DC energy to high-power or vitality DC-energy, which reduces the voltage pressure over the power electronics switching units and undulation is improving execution of the electrical system vitality efficiently and simplifying the circuit nature.Â